(untitled) (Research, Society and Development, 2021)
Objective: This study aimed to evaluate the in vitro performance of three different finishing and polishing systems, concerning providing better surface smoothness. Materials and methods: 2x4 mm specimens were made with 6 composites: Filtek Z250, Classic Herculite, Opalis, Filtek Z350, Zirconfilll and Estelite Omega, which were subsequently divided into four groups according to a different finishing system (Sof-Lex, OptiDisc, Praxis and Control). After polishing, twelve specimens were distributed to each of the six resins studied, making a total of 72 samples (n = 3), which had their roughness evaluated by a contact roughnessmeter. The Kruskal-Wallis test and Dunn’s post-test with Bonferroni adjustment were used to search for significant differences. Values ​​were considered significant when p <0.05. Results: The roughness values ​​for finishing systems showed statistical differences between OpiDisc x Praxis (p = 1,000), OpiDisc and Sof-lex (p = 0.605) and Control and all systems (p <0.0001). There was no statistical difference when analyzing the combination of resin x system. The Mylar strip provided surface quality. Conclusions: The size, composition and shape of the filler influenced the surface. Sof-lex and Praxis showed similar results, thus being a good choice for polishing. Clinical Relevance: This study aimed to help the professional in the choice of a better material in the polishing step.